METHOD FOR THE PREDICTION OF THE DEVELOPMENT OF CHRONIC PULMONARY HEART IN COAL WORKERS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - O. Yu. Korotenko (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
452 miners at the age of40-55years (average age is 50,9 ± 0,2 years) with chronic obstructive pulmonary disease were studied. Chronic pulmonary heart was detected in 289 patients (63,9 %). Using Bayes' method based on the determination of prognostic factors we have elaborated the technique for the prediction of the development of chronic pulmonary heart in miners with chronic obstructive pulmonary disease. The technique is based on the presence of respiratory insufficiency, associated ischemic heart disease and arterial hypertension, blood groups by AB0, MN, and P systems, some structural and functional indicators of heart (a myocardium mass index of aortic ventricle heart, an index of relative thickness of walls of aortic ventricle heart, an index of sphericity of aortic ventricle heart and an average pressure in a pulmonary artery). The use of genetic markers of blood groups by AB0, MN, and P systems allows more detailed estimate genetic predisposition to disease. By increasing the number of analyzed factors influencing the development of chronic pulmonary heart and using of additional markers, we have more accurate prediction of this complication. All figures are reduced in the general prognostic table. The work with the table is the following, it is necessary to sum up all the prognostic coefficients taking into account a sign. At the value of total amount of+6 points or more predisposition to development of chronic pulmonary heart for a worker is more predicted, at the sum less than -6 points we predict the resistance to development of chronic pulmonary heart, at intermediate values the forecast is not defined. The main advantage of the technique is speed and minor material costs. So, while conducting a single assessment of the health of miners with chronic obstructive pulmonary disease in outpatient and polyclinic conditions it is simply to select a group of persons at high risk of developing chronic pulmonary heart for timely preventive actions.